Design of Covid-19 Sterilization Room in Packages using Atmega328p Microcontroller Based Nozzle Spray - Okta Canda Pritiwi (Sunan Kalijaga Journal of Physics, 2022)
Efforts to prevent the spread of COVID-19 have been carried out, one of which is by using disinfectant fluids. The use of disinfectant liquid is widely used on objects, one of its uses is for spraying disinfectant on shipping packages in the form of goods which are still mostly done manually. In this research, it is necessary to develop a disinfectant spray tool for shipping goods with a sprayer that moves automatically in the form of a COVID-19 sterilization chamber in the package using a spray nozzle based on the ATmega328P microcontroller. This research is limited to item size 20 x 20 x 5 cm and object detection distance of 1 – 20 cm. The tests include testing the proximity sensor, programming stepper motors and pumps, testing the mass of goods, and the system as a whole. Proximity sensor testing results for a detection distance of 1 – 20 cm obtained an error at a distance of 1 and > 15 cm, while for a detection distance of 10 - > 400 cm an error was obtained from 0 - 3.41%. The results of the stepper motor programming test for readers at a distance of 1-20 cm when the motor is on. The results of the pump programming test for object detection distances of 1-20 cm when the motor is on. The results of testing the maximum mass of goods 2100 grams. The overall test results obtained 6 out of 10 tests were successful where the indicator of success was when all surfaces of the goods were completely wetted by the disinfectant liquid and limited to items measuring ≤ 20 x 20 x 5 cm.